Download as docx, pdf, or txt
Download as docx, pdf, or txt
You are on page 1of 5

Full-Name: Dư Gia Phú

ID card: QE170061
Class: AI17C

Page 279:
4:
1(1+1) 2
a) I3 = ( 2 )

b )Left side: 13 = 1
1(1+1) 2
Right: ( )2 = ( ))2 = 1
2 2

b) P(k) holds for arbitrative integer k ≥ 1


13 + 23 + …+ k3 = (𝑘(𝑘+1))2
2
c) I need to prove P(k) - > P(k + 1)
d) P(k + 1): 13 + 23 + …+ k3 + (k + 1)3 = ((𝑘+1)(𝑘+2))2
2
Assume P(k) is True
13 + 23 + …+ k3 + (k + 1)3 = (𝑘(𝑘+1))2 + (k + 1)3
2
𝑘2(𝑘+1) 𝑘 (𝑘+1) +4(𝑘+1)3
2 2
=( (𝑘+1)2(𝑘2+4(𝑘+1)
) +(k + 1) =
3
2
4 4 = 4
2 2 2 2
(𝑘+1) (𝑘 +4𝑘+4) (𝑘+1) (𝑘+2) ((𝑘+1)(𝑘+2))2
= 4 = 4 = 4
e)
Because (n(n+1)/2)2 always ≥ 0. So, if n is a negative integer,
13 + 23 + …+ n3 will be a negative number, it will False if use
formula.

Page 280:
6) Let P(n) = 1.1! + 2.2! + …. + n.n! = (n+1)! -1
P(1) is true since 1.1! = 1 = (1+1)! -1
= 2! -1 = 2 -1 = 1.
Assume P(n) is true for some n. (Induction Hypothesis)
Then we have to show that P(n+1) is true
1.1! + 2.2! + …. + n.n! + (n+1)(n+1)! = (n+1)! -1 + (n+1)(n+1)!
= (n+1)! [1 + n+1 ] -1
= (n+1)![n+2] -1
= (n+2)! -1
= ((n+1) +1)! -1
15)
Let P (n) be the given statement.
P (n) : 1.2 + 2.3 + 3.4 + ..... + n. (n + 1) = n (n + 1)(n + 2)/3
For n = 1,
P (1) :1.2 = [1 (1 + 1)(1 + 2)/3]
2 = 1.2.3/3
2 = 2, which is true.
Assume that P (k) is true for some positive integer k.
i.e., 1.2 + 2.3 + 3.4 + .... + k. (k + 1) = [k (k +1)(k + 2)]/3.....(1)
We will now prove that P (k +1) is also true.
Now, we have,
1.2 + 2.3 + 3.4 + ..... + (k + 1) [(k + 1) + 1]
= [1.2 + 2.3 + 3.4 + ..... + k.(k + 1)] + (k + 1)(k + 2)
= [k (k + 1)(k + 2)/3] + (k + 1)(k + 2) .....[from (1)]
= (k + 1) (k + 2) [k/3 + 1]
= (k + 1) (k + 2) (k + 3) /3
= {(k + 1) [(k + 1) + 1] [(k + 1) + 2]}/3
Thus P (k + 1) is true, whenever P (k) is true.
So: 1.2 + 2.3 + …+ n(n + 1) = 1(𝑛+1)(𝑛+2)
3

18)
a) First, Let P(n) be the statement that n! < nn
where n ≥ 2 is an integer (This is because we want the statement of P(2).
In this case the statement would be (n = 2): P(2) = 2! < 2^2

b) Now to prove this, let's complet the basis step:


We know that 2! = 2 * 1 = 2
and 2^2 = 2 * 2 = 4
Therefore: 2 < 4
c) For this part, we'll say that the inductive hypothesis would be
assuming that k! < k^k for some k ≥ 1

d) In this part, the only thing we need to know or prove is to


show that P(k+1) is also true, given the inductive hypothesis in
part c.

e) To prove that P(k+1) is true, let's solve the inductive hypothesis of k!


< k^k:
(k + 1)! = (k + 1)k!
(k + 1)k! < (k + 1)^k < (k + 1)(k + 1)^k
Since k < k+1 we have:
= (k + 1)^k+1
f) Finally, as the base and inductive steps are completed, the inequality
is true for any integer for any n ≥ 1. If we had shown P(4)
as our basis step, then the inequality would only be proven for n ≥ 4.
Page 308:
2)
a) f(n + 1) = -2f(n) and f(0) = 3
f(1) = -6 , f(2) = 12, f(3) = -24, f(4)= 48, f(5) = -96
b) f(n + 1) = 3f(n) + 7 and f(0) = 3
f(1) = 16 , f(2) = 55, f(3) = 172, f(4)= 523, f(5) = 1576
c) f(n + 1) = f2(n) – 2f(n) - 2 and f(0) = 3
f(1) = 1 , f(2) = -3, f(3) = 13, f(4)= 48, f(5) = 141
d) f(n + 1) = 3f(n)/3 and f(0) = 3
f(1) = 3 , f(2) = 3, f(3) = 3, f(4)= 3, f(5) = 3
8)
a) an + 1 = an + 4
b) an + 1 = 2 - an
c) an + 1 = an + 2(n + 1)
d) an+1 = an + (2n + 1)
12)
For Fn is true with n = k
F12 + F 22+ F 32 +…+ F 2k = F Fk K+1

For n = k+1
F12 + F 22+ F 32 +…+ F 2k + F k+1 2
= F12 + F 22+ F 32 +…+ F 2k + F k+1 2
= Fk FK+1 + Fk+12
= (Fk+1)(FK + FK + 1)
=FK+1 .FK+2
=FK+1.F(K+1)+1
Hence it is true for n = k +1 also by the principle of mathematical
induction, it is true for any n ≥ 1

Page 209:
34)
a) 1010
b) 11011
c) 111010010001

You might also like